Protests as Strategic Games: Experimental Evidence from Hong Kong's Antiauthoritarian Movement. Issue 2 (21st January 2019) - Cantoni, Davide; Yang, David Y; Yuchtman, Noam; Zhang, Y Jane
Abstract: Social scientists have long viewed the decision to protest as strategic, with an individual's participation a function of their beliefs about others' turnout. We conduct a framed field experiment that recalibrates individuals' beliefs about others' protest participation, in the context of Hong Kong's ongoing antiauthoritarian movement. We elicit subjects' planned participation in an upcoming protest and their prior beliefs about others' participation, in an incentivized manner. One day before the protest, we randomly provide a subset of subjects with truthful information about others' protest plans and elicit posterior beliefs about protest turnout, again in an incentivized manner. After the protest, we elicit subjects' actual participation. This allows us to identify the causal effects of positively and negatively updated beliefs about others' protest participation on subjects' own turnout. In contrast with the assumptions of many recent models of protest participation, we consistently find evidence of strategic substitutability. We provide guidance regarding plausible sources of strategic substitutability that can be incorporated into theoretical models of protests.